Hydrogen‐rich water regulates effects of ROS balance on morphology, growth and secondary metabolism via glutathione peroxidase in Ganoderma lucidum - Ang Ren; Rui Liu; Zhi‐Gang Miao; Xue Zhang; Peng‐Fei Cao; Tian‐Xi Chen; Chen‐Yang Li; Liang Shi; Ai‐Liang Jiang; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum is one of the most important medicinal fungi, but the lack of basic study on the fungus has hindered the further development of its value. To investigate the roles of the redox system in G. lucidum , acetic acid (HAc) was applied as a reactive oxygen species (ROS) stress inducer, and hydrogen‐rich water (HRW) was used to relieve the ROS stress in this study. Our results demonstrate that the treatment of 5% HRW significantly decreased the ROS content, maintained biomass and polar growth morphology of mycelium, and decreased secondary metabolism under HAc‐induced oxidative stress. Furthermore, the roles of HRW were largely dependent on restoring the glutathione system under HAc stress in G. lucidum . To provide further evidence, we used two glutathione peroxidase (GPX)‐defective strains, the gpxi strain, the mercaptosuccinic acid (MS, a GPX inhibitor)‐treated wide‐type (WT) strain, and gpx overexpression strains for further research. The results show that HRW was unable to relieve the HAc‐induced ROS overproduction, decreased biomass, mycelium morphology change and increased secondary metabolism biosynthesis in the absence of GPX function. The gpx overexpression strains exhibited resistance to HAc‐induced oxidative stress. Thus, we propose that HRW regulates morphology, growth and secondary metabolism via glutathione peroxidase under HAc stress in the fungus G. lucidum . Furthermore, our research also provides a method to study the ROS system in other fungi.

Alterations and correlations of the gut microbiome, metabolism and immunity in patients with primary biliary cirrhosis - Long‐Xian Lv; Dai‐Qiong Fang; Ding Shi; De‐Ying Chen; Ren Yan; Yi‐Xin Zhu; Yan‐Fei Chen; Li Shao; Fei‐Fei Guo; Wen‐Rui Wu; Ang Li; Hai‐Yan Shi; et al. (Environmental Microbiology, 2016)
Summary We selected 42 early‐stage primary biliary cirrhosis (PBC) patients and 30 healthy controls (HC). Metagenomic sequencing of the 16S rRNA gene was used to characterize the fecal microbiome. UPLC‐MS/MS assaying of small molecules was used to characterize the metabolomes of the serum, urine and feces. Liquid chip assaying of serum cytokines was used to characterize the immune profiles. The gut of PBC patients were depleted of some potentially beneficial bacteria, such as Acidobacteria, Lachnobacterium sp., Bacteroides eggerthii and Ruminococcus bromii , but were enriched in some bacterial taxa containing opportunistic pathogens, such as γ‐Proteobacteria, Enterobacteriaceae, Neisseriaceae, Spirochaetaceae , Veillonella , Streptococcus , Klebsiella , Actinobacillus pleuropneumoniae , Anaeroglobus geminatus , Enterobacter asburiae , Haemophilus parainfluenzae , Megasphaera micronuciformis and Paraprevotella clara . Several altered gut bacterial taxa exhibited potential interactions with PBC through their associations with altered metabolism, immunity and liver function indicators, such as those of Klebsiella with IL‐2A and Neisseriaceae with urinary indoleacrylate. Many gut bacteria, such as some members of Bacteroides, were altered in their associations with the immunity and metabolism of PBC patients, although their relative abundances were unchanged. Consequently, the gut microbiome is altered and may be critical for the onset or development of PBC by interacting with metabolism and immunity.

Identification of a putative cognate sensor kinase for the two‐component response regulator HrpG , a key regulator controlling the expression of the hrp genes in X anthomonas campestris pv. campestris - Rui‐Fang Li; Guang‐Tao Lu; Lei Li; Hui‐Zhao Su; Guo‐fang Feng; Ya Chen; Yong‐Qiang He; Bo‐Le Jiang; Dong‐Jie Tang; Ji‐Liang Tang (Environmental Microbiology, 2014)
Summary The bacterial phytopathogen X anthomonas campestris pv. campestris ( Xcc ) relies on the hrp (hypersensitive response and pathogenicity) genes to cause disease and induce hypersensitive response ( HR ). The hrp genes of bacterial phytopathogens are divided into two groups. Xcc hrp genes belong to group II . It has long been known that the group II hrp genes are activated by an AraC ‐type transcriptional regulator whose expression is controlled by a two‐component system ( TCS ) response regulator (named HrpG in Xcc ). However, no cognate sensor kinase has yet been identified. Here, we present evidence showing that the Xcc open‐reading frame XC _3670 encodes a TCS sensor kinase (named HpaS ). Mutation of hpaS almost completely abolished the HR induction and virulence. Bacterial two‐hybrid and protein pull‐down assays revealed that HpaS physically interacted with HrpG . Phos‐tag™ SDS‐PAGE analysis showed that mutation in hpaS reduced markedly the phosphorylation of HrpG in vivo . These data suggest that HpaS and HrpG are most likely to form a TCS . We also showed that XC _3669 (named hpaR2 ), which is adjacent to hpaS and encodes a putative TCS response regulator, is required for full virulence but not HR induction. HpaR2 also physically interacted with HpaS , suggesting that HpaS may also form another TCS with HpaR2 .